The Lion Air JT610 Crash Due to Lack of Pilot Training: Is There Responsibility for Indonesia? - Ghaisani, Amalina; Sefriani, Sefriani; Safitri, Alya Ananda (Faculty of Law, Universitas Jambi, 2024)
This research analyses international law, specifically in the realm of international aviation law. This research aims to determine whether Indonesia is responsible for the crash of Lion Air JT610 that happened on October 29, 2018. The accident was also followed five months later by the crash of Ethiopian Airlines ET302 on March 10, 2019. Both crashes involved the Boeing 737 MAX 8 and were linked to inadequate pilot training on the new Maneuvering Characteristics Augmentation System (MCAS). Using the normative legal research with statutory and case approach, the findings proved that besides its responsibility as a regulator, Indonesia is only responsible for issuing the airworthiness certificate, supervision, and investigation. On the other hand, the responsibility to ensure the maximum level of flight safety remains in the hands of the manufacturer company, including conducting pilot training and providing information regarding the new system.